Message - Arı, Dr. Nuray (Universal Journal of Pharmaceutical Research, 2023)
A warm welcome to the readers and the authors, We are happy to announce that our new issue has been published. Thank you for visiting UJPR website. I hope you all enjoy reading this issue. UJPR is an open access journal and continues growing. We always appreciate reviewers and editors for their hard work, and welcome any comments and suggestions to improve the quality of the journal. Free online article access can facilitates full-text searching, indexing, data storing, and other forms of processing and analysis. Everyone can copy, distribute, and source is appropriately cited. On the other hand, Pharmaceutical Sciences are one of the most important sciences to be considered nowadays. Simultaneously, interdisciplinary fields have enlarged giving hopes to patients worldwide to cure the diseases. The quality and content of UJPR has increased. After over tree years of living with COVID-19, we are learning to adapt to a world with this disease. COVID-19 has not only created severe panic among the people but also challenged the social culture and healthcare infrastructure all over the world. Development of new vaccines to control COVID-19 has changed the understanding of exploring vaccines, besides leading to great revolutionary modifications in the development of vaccines.We know protection from a booster decreases over time. The second booster may be more important. On the other hand, in some people, post-COVID-19 syndrome lasts months or years or causes disability. Long COVID is real and it is a condition which is still being studied. These ongoing health problems are sometimes called post-COVID-19 syndrome, post-COVID conditions, long COVID-19, long-haul COVID-19, and post acute sequelae of SARS COV-2 infection (PASC), need more investigation. Warm regards,